2011
DOI: 10.2319/121210-717.1
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric measurements from 3D reconstructed images compared with conventional 2D images

Abstract: Objective: To assess whether the values of different measurements taken on three-dimensional (3D) reconstructions from cone-beam computed tomography (CBCT) are comparable with those taken on two-dimensional (2D) images from conventional lateral cephalometric radiographs (LCRs) and to examine if there are differences between the different types of CBCT software when taking those measurements. Material and Methods: Eight patients were selected who had both an LRC and a CBCT. The 3D reconstructions of each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 29 publications
2
36
0
3
Order By: Relevance
“…26,27 A high correlation between posterior airway size on cephalometric radiographs and pharyngeal volume measured on tomographic scans has been reported. 28 Furthermore, Miles et al 29 reported a high reliability of identification of the commonly used cephalometric landmarks and measurements.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 A high correlation between posterior airway size on cephalometric radiographs and pharyngeal volume measured on tomographic scans has been reported. 28 Furthermore, Miles et al 29 reported a high reliability of identification of the commonly used cephalometric landmarks and measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Zamora et al [3] evaluated whether the angular and linear measurements of 3D reconstructions obtained from CBCT are equal to those of 2D images obtained from the cephalograms using two different software packages (Beta Nemoceph 3D, Software Nemotec, SL, Madrid, Spain, and In vivo 5 Anatomage, San Jose, CA). In this study, no statistically significant differences were found for 2D and 3D generated cephalograms.…”
Section: Intra-observer Reproducibilitymentioning
confidence: 99%
“…[3,4,6,7] Additionally, one of the most common insufficiencies of 2D methods with lateral cephalometric radiography and cephalometric analysis is double imaging of the lower borders of the mandible. Therefore, observer identification errors are also common in orthodontic anatomical landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies did not validate CBCT image superiority over 2-D lateral cephalograph. 10,13,14 Even in a rigorous test against the gold standard of caliper measurements on dry skulls, CBCT measurements were deemed clinically accurate, although the mean percent measurement error for CBCT images was 2.31% compared to 0.63% for calipers. 15 CBCT overcomes the sources of error in conventional 2-D radiographs: relatively low resolution, magnification error, image distortion and superimposition of structures.…”
Section: Cbct Accuracy and Reliability -Cephalometricsmentioning
confidence: 99%